Walls within Walls - Sherry, Maureen; Stower, Adam (New York : Katherine Tegen Books, 2012)
When the Smithfork family moves into a lavish Manhattan apartment building, they discover clues to a decades-old mystery hidden behind the walls of their new home.
Reprint. Originally published: c2010.
Includes bibliographical references.
Keywords: Siblings -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction